2021
DOI: 10.1371/journal.pone.0250007
|View full text |Cite
|
Sign up to set email alerts
|

Reporting in clinical studies on platelet-rich plasma therapy among all medical specialties: A systematic review of Level I and II studies

Abstract: Background The clinical practice of platelet-rich plasma (PRP) therapy has grown significantly in recent years in multiple medical specialties. However, comparisons of PRP studies across medical fields remain challenging because of inconsistent reporting of protocols and characterization of the PRP being administered. The purpose of this systematic review was to determine the quantity of level I/II studies within each medical specialty and compare the level of study reporting across medical fields. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The exact mechanism of PRP action remains unclear and is even sometimes questioned [ 61 , 62 ]. It is speculated that PRP enhances wound healing because of the presence of various cytokines, including growth factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanism of PRP action remains unclear and is even sometimes questioned [ 61 , 62 ]. It is speculated that PRP enhances wound healing because of the presence of various cytokines, including growth factors.…”
Section: Resultsmentioning
confidence: 99%
“…PRP also presents hemostatic properties. Moreover, it may indirectly activate macrophages via serotonin and histamine release, which increase the capillary permeability, consequently leading to the inflammatory cells’ access [ 56 , 61 , 62 ]. Finally, PRP in in vitro studies has been found to stimulate the chondrocytes to engineer the cartilage and the biosynthesis of collagen and proteoglycans [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRP has been the subject of extensive research in the medical fields of orthopaedics, plastic surgery, and maxillofacial surgery, where it has multiple clinical applications [16]. Recent research focuses on neural regeneration and chronic pain [17].…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…Recently, Jaron Nazaroff et al published ( 12 ) a systematic review and Meta-Analysis (Cochrane Database, PubMed, and EMBASE databases) for level I/II clinical studies on PRP injections across all medical specialties [cardiothoracic surgery, cosmetic, dermatology, musculoskeletal (MSK), neurology, oral maxillofacial surgery, ophthalmology, and plastic surgery]. Generally, 61% of the studies found PRP to be favorable over control treatment, with no difference across medical specialties.…”
Section: Introductionmentioning
confidence: 99%